Предмет: Математика,
автор: vicifuf1246
|1. (6 баллов) Упрости выражение (2y — 1) (2y + 1) - (3y+1) + 5у(у + 3)
и вычисли его значение, если у = -4.
Ответ:
Помогите пожалуйста решить
Ответы
Автор ответа:
2
Ответ:
Пошаговое объяснение:
(2y — 1) (2y + 1) - (3y+1) + 5у(у + 3)=4у²+2у-2у-1-3у-1+5у²+15у=9у²+12у-2
9*(-4)²+12*(-4)-2=144-48-2=94
vicifuf1246:
Спасибо)))
Похожие вопросы
Предмет: Литература,
автор: aisi47
Предмет: Математика,
автор: ulanakoshiretss
Предмет: Українська мова,
автор: pancukhristina80
Предмет: Математика,
автор: himikDaniil1
Предмет: Математика,
автор: 5TANYA14